Humanoid robot simulator: a realistic dynamics approach - A. Paulo Moreira (2008)
This paper describes a humanoid robot simulator with realistic dynamics. Assimulation is a powerful tool for speeding up the control software development, thesuggested accurate simulator allows to accomplish this goal. The simulator, based on theOpen Dynamics Engine and GLScene graphics library, provides instant visual feedbackand allows the user to test any control strategy without damaging the real robot in theearly stages of the development. The proposed simulator also captures somecharacteristics of the environment that are important and allows to test controllers withoutaccess to the real hardware. Experimental results are shown that validate this approach